The Female Figures And Participants Of The Armenian Liberation Movement In The Memoirs Of Vardan Of Khanasor - Sahakyan, Ruben (ՀՀ ԳԱԱ)
Since the 80s of the 19th century, Armenian women and girls played an active role in the Armenian liberation movement against the Ottoman despotism. Based on the memoirs of one of the most prominent figures of the liberation movement, Vardan of Khanasor (Sargis Mehrabyan, 1867-1943), the article presents the women and girls, who fought against the Ottoman despotism almost equally with men. In his memoirs, he presents the women and girls of the Province of Salmast in Northern Iran, and the Van Province, who helped the Hajduks with all their might. Vardan recalls teachers Mariam Makaryan and Satenik Ohanjanyan, who also held cultural events by organizing various circles for women and girls. Among the feminine persons from the Province of Van, Vardan of Khanasor focuses on Zaruhi Teroyan, who was sentenced by the Turkish authorities to seven years in prison for her active liberation activities.
Keywords: History